Avaliação de emendas soldadas em perfis laminados sujeitos à flexão estática - Machado, Sandro Clodoaldo (2013)
Rolled shapes are produced in gauges from 150 to 610mm in Brazil, in two different lengths, 9.000 and 12.000mm. In most cases these lengths must be adjusted in accordance with those proposed in specific projects, making it necessary to cut them, producing important losses. An alternative is to use the part not used joining them with welded splices. In the present work were evaluated experimentally the behavior of rolled shapes with butt welds splices subjected to simple static bending, with the goal to verify the performance compared to the sections without welded splices